2016
DOI: 10.1159/000443989
|View full text |Cite
|
Sign up to set email alerts
|

Mental State Decoding in Adolescent Boys with Major Depressive Disorder versus Sex-Matched Healthy Controls

Abstract: Background: Several adult depression studies have investigated mental state decoding, the basis for theory of mind, using the Reading the Mind in the Eyes Test. Findings have been mixed, but a comprehensive study found a greater severity of depression to be associated with poorer mental state decoding. Importantly, there has yet to be a similar study of adolescent depression. Converging evidence suggests that atypical mental state decoding may have particularly profound effects for psychosocial functioning amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…Enhanced mental state decoding was reported in a recent study [39] among depressed adolescent boys on the Child Eyes Test [40], an adapted version of the RMET, compared to sex-matched healthy controls. The MDD group performed significantly better than the control group on the whole, but specifically they were more accurate than the controls at identifying negatively valenced items.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Enhanced mental state decoding was reported in a recent study [39] among depressed adolescent boys on the Child Eyes Test [40], an adapted version of the RMET, compared to sex-matched healthy controls. The MDD group performed significantly better than the control group on the whole, but specifically they were more accurate than the controls at identifying negatively valenced items.…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, a number of studies have not reported significant between-group differences between MDD patients and healthy controls [42,53,55,57,58] or found minimal differences [35]. Adolescent boys with MDD were actually found to be better at mental state decoding than healthy adolescent boys [39]. It should be noted that the number of participants in several of these studies has been rather small [35,42,45,53,55,57,58,68].…”
Section: Discussionmentioning
confidence: 99%
“…The only study conducted so far in adolescent MDD about mental state decoding reported that adolescent boys with MDD performed significantly better than healthy controls (Mellick & Sharp, 2016). But this study differs from majority of findings in adults and adolescents (Lenti et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However adult studies are pointing mostly to possible deficits in all three orders of the social cognitive functioning in MDD (Bora & Berk, 2016), child and adolescent studies have found conflicting results. Among the limited number of studies investigating social cognition in adolescents' depression, while Mellick et al found enhanced mental state decoding among adolescent boys with depression (Mellick & Sharp, 2016), in two other studies examining the recognition of facial expressions, Schepman et al reported no overall or specific deficits in facial expression recognition (Schepman et al, 2012) and Lenti et al reported failure to recognize negative-aroused facial expressions in children and adolescents with depression (Lenti et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Of the few studies directly comparing ToM performance across diagnostic groups, most were limited to a comparison between two groups. For example, Purcell et al (2013) found comparable ToM impairments between remitted BD and MDD patients, while a number of other studies did not find significant ToM impairment in MDD patients (Bazin et al, 2009;Berecz et al, 2016;Mellick and Sharp, 2016;Wilbertz et al, 2010), even a better ToM performance was found in depressed adolescent boys (Mellick and Sharp, 2016) and woman with a maternal history of depression (Harkness et al, 2011). Similarly, previous studies comparing ToM performance in SCZ with BD patients suggested that SCZ patients might be more impaired in ToM than BD patients (Caletti et al, 2013;Guastella et al, 2013;Lahera et al, 2015) while some studies reported similar extent of ToM impairment in these two groups of patients (Donohoe et al, 2012;Thaler et al, 2013) .…”
Section: Introductionmentioning
confidence: 94%